Economic dispatch using genetic algorithm / Sahzani Sarip - Sarip, Sahzani (2001)
This project presents an alternative method of solving Economic Dispatch (ED) by using Genetic Algorithm (GA). Although several methods of ED could be considered, the study focused on the total generation cost and the incremental cost. The proposed method was applied to a three and four generating system. The results obtained were compared with the classical method to show its feasibility.